Perioperative Acute Kidney Injury in Cardiac Surgery (Bangladesh Heart Journal, 2016)
Acute kidney injury (AKI) is a relatively common complication, occurs in up to 30% of all patients in cardiac surgery and requires dialysis in approximately 2% of patients. The development of AKI after cardiac surgery is associated with increased morbidity and mortality. AKI is caused by a variety of factors, including nephrotoxins, hypoxia, mechanical trauma, inflammation, cardiopulmonary bypass and hemodynamic instability and it may be affected by the clinicians choice of fluids and vasoactive agents as well as the transfusion strategy used. More timely diagnosis would allow for earlier intervention and could improve patient outcomes. Currently, there are no active treatments for AKI. Therefore, In-depth knowledge of the risk factors and pathogenesis for AKI offers some guidance for the prevention and management of AKI.Bangladesh Heart Journal 2015; 30(2) : 78-86